Hybrid and adaptive sectors P&O MPPT algorithm based wind generation system - Mousa, Hossam H.H.; Youssef, Abdel-Raheem; Mohamed, Essam E.M. (Renewable energy, 2020)
This article suggests a new adaptive perturb and observe (AD-PO) and hybrid P&O (HB-PO) maximum power point tracking (MPPT) algorithms based on the variable speed - wind energy conversion system (WECS) to overcome drawbacks of conventional step-size P&O (CPO) algorithms and to improve the tracking performance of variable step-size P&O (VS-PO) algorithms. Both AD-PO and HB-PO algorithms divide the power-speed (P-ω) curve into modular sectors by estimating the distance between the actual and optimum rotor speed. Furthermore, the limits of operating sectors are continuously modified according to the optimal rotor speed variations. The AD-PO intelligently adapts the perturbation step-size to cope with the rapid wind speed fluctuations, which enables to accurate maximum power point (MPP) tracking. The proposed HB-PO combines the rapid tracking speed and low oscillation levels by specifying number of sectors to operate with VS-PO strategy while remaining sectors to operate with the AD-PO strategy. Moreover, a smart wind speed-sensorless scheme has been established to eliminate the installation of mechanical sensors. Simulation results verify that proposed P&O algorithms offer a 4.0% increase in the WECS efficiency over the conventional algorithm. The effectiveness of proposed control schemes is confirmed by real wind data (Boulder City, Colorado) using MATLAB/SIMULINK environment. •An adaptive and hybrid P&O algorithms are proposed for Multi-phase PMSG based WECS.•The proposed algorithms eradicate the limitations of the existing P&O algorithms.•The proposed algorithms use adaptive and hybrid step-sizes with modular sectors.•The proposed algorithms exhibit fast response with low steady-state oscillations.•The proposed algorithms yield an 4.0% increase in the efficiency.